Moscow Rules? 'Red' Unionism and 'Class Against Class' in Britain, Canada, and the United States, 1928-1935 - Manley, John (Labour / Le Travail, 2005)
The article analyzes the claims of traditionalist and revisionist historians concerning communism by comparing industrial work of the national socialist parties in Great Britain, the U.S. and Canada in the period 1928-1935. The efforts made by the national parties to strive for leadership of the working class in the workplace are explored. Traditionalist historians are of the opinion that adequate comprehension of communism requires recognition of subordination of each national party to the demands of Moscow, Russia. According to revisionist historians, the national parties enjoyed autonomy in resisting or adapting to the demands of Moscow.
Keywords: Canada; Communism; Comparative studies; GREAT Britain; Labor Unions; SOCIALIST parties; United States; Working class

"Audacity, audacity, still more audacity": Tim Buck, the Party, and the People, 1932-1939 - Manley, John (Labour / Le Travail, 2002)
In 1932, when Communist Party of Canada (CPC) general secretary Tim Buck, six other CPC leaders and one unfortunate rank-and-filer began lengthy sentences in Kingston penitentiary, the Party seemed to have reached its nadir. In fact, martyrdom proved to be a springboard for sustained political revival and was a particular boon to Buck, helping him consolidate a stirring performance in the dock at the Party trial a few months earlier. Until then, he had been considered something of a mediocrity, his status dependent almost entirely upon Moscow's grace and favour. During his three years in Kingston prison, the underground Party successfully reinvented him as the "dauntless leader of the Canadian working class": shortly after his release in November 1934, his five month-long coast-to-coast tour attracted (by the RCMP's almost certainly conservative estimate) a total audience of over 100,000. Buck proceeded to dominate the Party for the remainder of the decade — the Popular Front years — a period fondly recalled in his posthumous memoirs. Buck presented the Popular Front strategy as his — as much as "Moscow's" — invention and quietly attributed the Party's rise in fortunes (membership almost tripled) in large part to his bold and independent political leadership. The Popular Front was certainly good news for Buck, but whether it was good news for "Tim Buck's Party" is more open to question. This paper questions Buck's self-evaluation and suggests that the exposure of the cynical character of the Popular Front project in 1939 "may have planted the seeds of [the] Party's long postwar decline."